The formation mechanism and failure mode of a talus slope induced by rockfalls in Nayong County, Southwest China - Yang, Hufeng; Xing, Bencong; He, Jiangkun; Jiang, Hu; Cheng, Qiang (Frontiers in Earth Science, 2022)
Hillslope processes and mass movement are key issues in the analysis and evaluation of geological disasters in mountainous regions. A rockfall-dominated talus slope exhibits a typical outcrop-talus slope system as the product of detached blocks and rock fragments. The Zongling rockfall zone is one of the most active outcrop-talus slope systems in southwest China, and it provides a representative case study on the assessment of rockfall hazards at the base of talus slopes. In this paper, the formation mechanism and failure model of this rock-talus system were studied using field investigation, remote sensing image analysis, and numerical simulation. The findings reveal that the lithology and rock mass structure of the study site are controlling factors for outcrop retreat and the progressive development of talus deposits. This process is intensified by rainfall and mining activities. Boulder accumulation on the platform at the middle section of the talus slope serves as top loading for the slope mechanical system. During the boulder-ground interaction, the rockfall impact acts as toe cutting to change the geometry and mechanical balance of the talus slope. It was found that toe cutting significantly influenced slope stability, which led to a decrease in anti-sliding force of the slope. The slope failure induced by rockfalls occurred with the combined effect of top loading and toe cutting on this talus slope. During rockfall prevention and mitigation in this region, the government and residents should consider the geodisaster chain, as this relates to the impact of rockfall on talus slopes, in addition to the risk of damage due to the rockfall trajectory.